Genotypic Diversity and Genome-Wide Association Study of Protein Content and Amino Acid Profile in Diverse Potato Accessions - Haroon Rasheed; Yining Ying; Daraz Ahmad; Bowen Deng; Jinsong Bao (Foods, 2025)
The genotypic diversity and genome-wide association study (GWAS) of potato proteins and amino acid content were investigated in two environments: 98 potato accessions in Environment I and 93 in Environment II. Results revealed that aspartic acid was the most abundant amino acid in environment I and glutamic acid in environment II. The limiting amino acids were cysteine in both environments. The environmental variance accounted for more than 40% of the total variance for all traits except for serine and gamma amino butyric acid (GABA), indicating that potato protein and most amino acids were affected by growing seasons. GWAS identified 78 significant loci associated with potato protein and amino acid contents. The pleiotropic loci, especially those located on chromosomes 6, 9, and 11, provide a strong genetic basis for quality improvement. This study provides genetic insights into potato proteins and amino acid diversity, thereby enhancing molecular breeding for nutritional qualities.